A carbon-coated manganese selenide / manganese tungstate composite material with catalytic performance and a preparation method and application thereof

CN122895012APending Publication Date: 2026-10-13HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610833639.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]针对上述背景技术中存在的不足,本发明主要针对现有碳基材料用于隔膜修饰,但其非极性与多硫化物的极性间相互作用微弱,阻抑效果不佳的问题

Benefits of technology

本发明提供了一种具有催化性能的碳包覆硒化锰/钨酸锰复合材料及其制备方法和应用,本发明将Mn3O4/MnWO4与PDA进行简单机械混合后高温碳化硒化的方式制备MnSe/MnWO4@C,相较于现有的MnSe/MnWO4材料,本发明公开的制备方法工艺简单、制备周期短。另外,本研究中使用的PDA具有邻二苯酚和氨基官能团,碳化后仍能均匀包覆材料本身,提供一个强导电性碳壳的同时硒烧结过程中产生空位,从而能够有更多的活性位点,提高对多硫化物的吸附效果。采用MnSe/MnWO4@C改性隔膜的Li-S电池具有优异的电化学性能。这项工作为Li-S电池的商业应用提供了广阔的前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895012A_ABST
    Figure CN122895012A_ABST
Patent Text Reader

Abstract

The application discloses a carbon-coated manganese selenide / manganese tungstate composite material with catalytic performance and a preparation method and application thereof, and relates to the technical field of composite material preparation.The method comprises the following steps: uniformly dispersing manganese sulfate, ammonium persulfate and ammonium tungstate in an aqueous solvent to obtain a precursor solution, and then synthesizing Mn3O4 / MnWO4 microspheres through a hydrothermal method; stirring and reacting Mn3O4 / MnWO4 microspheres and dopamine hydrochloride in a Tris solution in the dark to obtain a Mn3O4 / MnWO4@PDA composite material; and performing carbonization treatment and selenization treatment on the Mn3O4 / MnWO4@PDA composite material to obtain the carbon-coated manganese selenide / manganese tungstate composite material.The MnO / MnWO4@C used in the application has excellent chemical adsorption and catalytic effect on polysulfides, and can effectively limit the "shuttle effect" of the polysulfides.The lithium-sulfur battery using the MnSe / MnWO4@C modified separator exhibits excellent electrochemical performance, has a high specific capacity, good cycle performance and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material preparation technology, specifically to a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, its preparation method, and its application. Background Technology

[0002] Among existing energy storage systems, lithium-sulfur (Li-S) batteries are a novel energy storage system due to their high theoretical specific capacity (1675 mAh / g) and theoretical energy density (2600 Wh / kg). Furthermore, the cathode material, elemental sulfur, is abundant, environmentally friendly, and inexpensive. However, the main obstacle to the development of current Li-sulfur batteries is the "shuttle effect" of polysulfides. During charge and discharge, elemental sulfur cathodes form soluble polysulfide intermediates, which diffuse from the electrolyte to the lithium anode and continuously deposit on its surface, increasing internal impedance and drastically reducing electrochemical performance. Therefore, suppressing the polysulfide shuttle effect is crucial for improving the overall performance of current Li-sulfur batteries. As a key component of Li-sulfur batteries, the commercially available polyolefin separators (PP, PE, or PP / PE) have relatively large pore sizes, making it easy for polysulfides to shuttle to the anode. Modifying the separator with a functional material is a relatively simple and effective way to suppress the polysulfide shuttle effect.

[0003] Membrane modification has become an important research direction due to its ability to enhance electron / ion transfer, improve electrolyte absorption, and inhibit polysulfide diffusion. Currently, carbon-based materials (such as graphene, carbon nanotubes, and mesoporous carbon) are often used for membrane modification, but the interaction between their nonpolarity and the polarity of polysulfides is weak, resulting in poor inhibition effects. Summary of the Invention

[0004] To address the shortcomings of the aforementioned background technologies, this invention primarily targets the problem that existing carbon-based materials used for membrane modification exhibit weak interactions between their nonpolarity and the polarity of polysulfides, resulting in poor inhibition effects. This invention provides a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, its preparation method, and its applications. The method involves uniformly coating Mn3O4 / MnWO4 onto a PDA followed by carbonization and high-temperature selenization treatment to obtain a carbon-coated MnSe / MnWO4@C composite material with excellent conductivity and polarity. When used for modifying lithium-sulfur battery membranes, this composite material effectively limits the "shuttle effect" of polysulfides through synergistic physical and chemical interactions, thereby significantly improving the electrochemical performance of lithium-sulfur batteries.

[0005] The first objective of this invention is to provide a method for preparing a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, comprising the following steps: Manganese sulfate, ammonium persulfate and ammonium tungstate were uniformly dispersed in an aqueous solvent to obtain a precursor solution, which was then used to synthesize Mn3O4 / MnWO4 microspheres via a hydrothermal method. Mn3O4 / MnWO4 microspheres and dopamine hydrochloride were reacted in Tris solution under light-protected stirring to obtain Mn3O4 / MnWO4@PDA composite material; The Mn3O4 / MnWO4@PDA composite material was carbonized to obtain MnO / MnWO4@C material; After mixing MnO / MnWO4@C material with a certain amount of selenium powder, it is subjected to selenization treatment in a high-temperature solid phase at 600~700°C to obtain carbon-coated manganese selenide / manganese tungstate composite material.

[0006] Preferably, the mass ratio of manganese sulfate, ammonium persulfate and ammonium tungstate is (1.35-1.55):(1.87-1.93):0.8.

[0007] Preferably, the hydrothermal synthesis process includes: sealing the precursor solution in a Teflon-lined stainless steel autoclave and holding it at 100~110℃ for 6~12h.

[0008] Preferably, the Tris solution is prepared by placing tris(hydroxymethyl)aminomethane powder in an aqueous solvent and stirring to prepare a solution with a pH of 8-9; the concentration of the Tris solution is 0.03-0.0312 mol / L; and the mass ratio of the Mn3O4 / MnWO4 microspheres to dopamine hydrochloride is 1:0.5-2.

[0009] Preferably, the carbonization process involves heating the gas to 600-700°C at a rate of 2-3°C / min under argon atmosphere, holding the temperature for 1-2 hours, and then cooling it to room temperature.

[0010] Preferably, the selenization process is carried out in a high-temperature solid phase, comprising: The MnO / MnWO4@C material is mixed with a certain amount of selenium powder and placed in a ceramic boat. The ceramic boat is placed in a tube furnace and heated to 600-700°C at a heating rate of 2-3°C / min under an argon atmosphere. After holding at this temperature for 1-2 hours, the temperature is lowered to room temperature.

[0011] Preferably, the mass ratio of the MnO / MnWO4@C material to selenium powder is 1:3 to 1:5.

[0012] The second objective of this invention is to provide a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties.

[0013] The third objective of this invention is to provide an application of a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties in the preparation of lithium-sulfur batteries.

[0014] Preferably, the polypropylene separator in the lithium-sulfur battery is modified using a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties. The modification process includes: A carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, acetylene black, and PVDF were mixed and ground in a mass ratio of (6~10):1:1. NMP was then added to prepare a uniform slurry, which was then uniformly coated onto a polypropylene separator used in lithium-sulfur batteries to obtain a modified separator.

[0015] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, its preparation method, and its applications. The invention prepares MnSe / MnWO4@C by a simple mechanical mixing of Mn3O4 / MnWO4 and PDA followed by high-temperature carbonization and selenization. Compared to existing MnSe / MnWO4 materials, the preparation method disclosed in this invention is simpler and has a shorter preparation cycle. Furthermore, the PDA used in this study possesses o-diphenol and amino functional groups, which allow for uniform coating of the material itself after carbonization, providing a highly conductive carbon shell while generating vacancies during selenium sintering, thus creating more active sites and improving the adsorption effect on polysulfides. Li-S batteries using MnSe / MnWO4@C modified separators exhibit excellent electrochemical performance. This work provides broad prospects for the commercial application of Li-S batteries. Attached Figure Description

[0016] Figure 1 These are X-ray diffraction patterns of MnSe / MnWO4@C prepared in Example 2 and the comparative counterexample MnSe@C; Figure 2 These are Raman plots of MnSe / MnWO4@C prepared in Example 2 and the comparative counterexample MnSe@C; Figure 3 These are SEM images of MnSe@C prepared in a comparative manner; Figure 4 This is a SEM image of MnO / MnWO4@C prepared in the preparation process (3) of Example 3; Figure 5 Here is a SEM image of MnSe / MnWO4@C prepared in Example 3; Figure 6 This is a comparison chart of the rate performance of the MnSe / MnWO4@C composite modified membrane prepared in Example 3 and the MnSe@C composite modified membrane prepared in the comparative example and the commercial membrane at different current densities; Figure 7 This is a comparison chart of the cycling performance of Li-S batteries with MnSe / MnWO4@C prepared in Example 3, MnSe@C composite material modified separator prepared in the comparative example, and commercial separator at 1 C current density. Detailed Implementation

[0017] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.

[0018] This invention addresses the important direction of membrane modification in existing lithium-sulfur batteries, which can enhance electron / ion transfer, improve electrolyte absorption, and inhibit polysulfide diffusion. Currently, carbon-based materials (such as graphene, carbon nanotubes, and mesoporous carbon) are often used for membrane modification, but the interaction between their nonpolarity and the polarity of polysulfides is weak, resulting in poor inhibition effects.

[0019] Therefore, the purpose of this invention is to provide a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, its preparation method, and its application. This method involves uniformly coating Mn3O4 / MnWO4 onto a PDA followed by carbonization and high-temperature selenization treatment to obtain a carbon-coated MnSe / MnWO4@C composite material with excellent conductivity and polarity. When used for modification of lithium-sulfur battery separators, this composite material effectively limits the "shuttle effect" of polysulfides through a synergistic physical and chemical action, thereby significantly improving the electrochemical performance of lithium-sulfur batteries.

[0020] The MnO / MnWO4@C used in this invention exhibits excellent chemisorption and catalytic activity towards polysulfides, effectively limiting the "shuttle effect" of polysulfides. Lithium-sulfur batteries using this MnSe / MnWO4@C modified separator demonstrate excellent electrochemical performance, exhibiting high specific capacity, good cycle performance, and rate performance.

[0021] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, comprising the following steps: Manganese sulfate, ammonium persulfate and ammonium tungstate were uniformly dispersed in an aqueous solvent to obtain a precursor solution, which was then used to synthesize Mn3O4 / MnWO4 microspheres via a hydrothermal method. Mn3O4 / MnWO4 microspheres and dopamine hydrochloride were reacted in Tris solution under light-protected stirring to obtain Mn3O4 / MnWO4@PDA composite material; The Mn3O4 / MnWO4@PDA composite material was carbonized to obtain MnO / MnWO4@C material; After mixing MnO / MnWO4@C material with a certain amount of selenium powder, it is subjected to selenization treatment in a high-temperature solid phase at 600~700°C to obtain carbon-coated manganese selenide / manganese tungstate composite material (MnSe / MnWO4@C).

[0022] This invention utilizes a hydrothermal high-temperature and high-pressure environment to process Mn.2+ With Mn 3+ During the synergistic hydrolysis and crystallization, ammonium tungstate dissociates to release WO4. 2- , with the remaining Mn in the solution 2+ MnWO4 was generated by combining with dopamine hydrochloride, and then polydopamine (PDA) was generated by oxidative self-polymerization. PDA was uniformly coated on Mn3O4 / MnWO4 by means of hydrogen bonding, π-π interaction and electrostatic adsorption. After carbonization and selenization treatment, carbon-coated manganese selenide / manganese tungstate composite material (MnSe / MnWO4@C) was obtained.

[0023] The mass ratio of manganese sulfate, ammonium persulfate, and ammonium tungstate is (1.35-1.55):(1.87-1.93):0.8.

[0024] The hydrothermal synthesis process includes: sealing the precursor solution in a Teflon-lined stainless steel autoclave and holding it at 100~110℃ for 6~12h.

[0025] The Tris solution is prepared by placing tris(hydroxymethyl)aminomethane powder in an aqueous solvent and stirring to obtain a solution with a pH of 8-9; the concentration of the Tris solution is 0.03-0.0312 mol / L. The mass ratio of the Mn3O4 / MnWO4 microspheres to dopamine hydrochloride is 1:0.5~2.

[0026] The carbonization process involves heating the gas to 600-700°C at a rate of 2-3°C / min under argon atmosphere, holding the temperature for 1-2 hours, and then cooling it to room temperature.

[0027] High-temperature solid-phase selenization treatment includes: The MnO / MnWO4@C material is mixed with a certain amount of selenium powder and placed in a ceramic boat. The ceramic boat is placed in a tube furnace and heated to 600-700°C at a heating rate of 2-3°C / min under an argon atmosphere. After holding at this temperature for 1-2 hours, the temperature is lowered to room temperature.

[0028] The mass ratio of the MnO / MnWO4@C material to selenium powder is 1:3 to 1:5.

[0029] An exemplary method for preparing a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties includes: Step 1: Add a certain amount of tris(hydroxymethyl)aminomethane (Tris) powder to 1000 mL of deionized water, stir evenly, and adjust the pH to about 8.5 to obtain a Tris solution. This provides the optimal conditions for the oxidative self-polymerization reaction of dopamine hydrochloride and provides conditions for uniform coating in step 3. Step 2: Dissolve 1.35-1.55 g MnSO4·H2O, 1.87-1.93 g (NH4)2S2O8, and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; (NH4)2S2O8 acts as a strong oxidant to partially oxidize the Mn in the system. 2+ Oxidized to Mn 3+ Under hydrothermal high temperature and high pressure environment, Mn 2+ With Mn 3+ During the synergistic hydrolysis and crystallization, ammonium tungstate dissociates to release WO4. 2- , with the remaining Mn in the solution 2+ Mn3O4 / MnWO4 microspheres were synthesized via a hydrothermal method by combining MnWO4 with the generated MnWO4. Step 3: Take a certain amount of Tris buffer solution (pH≈8.5), and weigh dopamine hydrochloride (DA) and Mn3O4 / MnWO4 material at a 1:1 mass ratio. Dopamine hydrochloride undergoes oxidative self-polymerization to generate polydopamine (PDA), which is then uniformly coated onto Mn3O4 / MnWO4 by means of hydrogen bonding, π-π interaction and electrostatic adsorption to obtain Mn3O4 / MnWO4@PDA solution by stirring in the dark. The Mn3O4 / MnWO4@PDA material is then subjected to carbonization reduction treatment in an argon atmosphere to dehydrate, dehydrogenate, and carbonize the PDA into a carbon layer to obtain MnO / MnWO4@C. Step 4: Mix MnO / MnWO4@C material with a certain amount of selenium powder and perform selenization treatment using high-temperature solid phase to obtain MnSe / MnWO4@C.

[0030] In step 1, the amount of Tris used is 3.63-3.78 g.

[0031] The stirring method used in step 1 is magnetic stirring, and the stirring time is 8 hours.

[0032] The specific method of the hydrothermal method used in step 2 is as follows: the formed precursor solution is sealed in a 100 mL Teflon-lined stainless steel autoclave, kept at 105 °C for 8 h, and then centrifuged, washed and dried to obtain Mn3O4 / MnWO4; wherein, the washing method is to wash several times with deionized water and anhydrous ethanol.

[0033] The high-temperature carbonization conditions in step 3 are as follows: under an argon atmosphere, the temperature is increased to 650°C at a heating rate of 2°C / min, held at that temperature for 1 hour, and then cooled to room temperature.

[0034] The high-temperature solid-state selenization method used in step 4 involves mixing and grinding MnO / MnWO4@C with selenium powder, then placing the mixture in a ceramic boat. The boat is then placed in a tube furnace, and under an argon atmosphere, the temperature is increased to 650°C at a rate of 2°C / min, held for 1 hour, and then cooled to room temperature. The mass ratio of MnO / MnWO4@C to selenium powder is 1:4.

[0035] Therefore, the preparation method provided by the present invention involves adding a certain amount of MnSO4·H2O, (NH4)2S2O8 and ammonium tungstate to 80 mL of deionized (DI) water; then mixing and magnetically stirring for 40 min, and sealing the solution in a 100 mL Teflon-lined stainless steel autoclave, keeping it at 105℃ for 8 h, and then centrifuging, washing and drying to obtain Mn3O4 / MnWO4; then treating Mn3O4 / MnWO4 by high-temperature solid-state carbonization in a tube furnace to obtain MnO / MnWO4@C; and then selenizing MnO / MnWO4@C by high-temperature solid-state carbonization in a tube furnace to obtain sample MnSe / MnWO4@C.

[0036] A second aspect of the present invention provides a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties.

[0037] A third aspect of this invention provides the application of a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties in the preparation of lithium-sulfur batteries.

[0038] Among them, carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties is used to modify the polypropylene separator in lithium-sulfur batteries. The modification process includes: A carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, acetylene black, and PVDF were mixed and ground in a mass ratio of (6~10):1:1. NMP was then added to prepare a uniform slurry, which was then uniformly coated onto a polypropylene separator used in lithium-sulfur batteries to obtain a modified separator.

[0039] For example, a method for preparing MnSe / MnWO4@C modified separators for lithium-sulfur batteries using MnSe / MnWO4@C composite materials involves mixing and grinding MnSe / MnWO4@C, acetylene black, and PVDF in a mass percentage ratio of 8:1:1, adding NMP to prepare a uniform slurry, and then uniformly coating it onto a commercial polypropylene separator for lithium-sulfur batteries to obtain the MnSe / MnWO4@C modified separator.

[0040] Therefore, the present invention involves mixing and grinding a certain amount of MnSe / MnWO4@C, acetylene black and binder polyvinylidene fluoride (PVDF), then adding N-methyl-2-pyrrolidone (NMP) to prepare a uniform slurry, which is then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to perform functional modification on the lithium-sulfur battery separator.

[0041] It should be noted that, unless otherwise specified, the experimental methods used in this invention are all conventional methods; and the reagents and materials used, unless otherwise specified, are all commercially available.

[0042] Example 1 Preparation of MnSe / MnWO4@C composite materials: 1): Add 3.73 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 1.35 g MnSO4·H2O, 1.88 g (NH4)2S2O8 and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 90°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 / MnWO4 microspheres. 3): Take 100 mL of Tris solution, weigh 50 mg of dopamine hydrochloride (DA) and 100 mg of Mn3O4 / MnWO4 material, add them to the Tris solution and stir in the dark to obtain polydopamine-coated Mn3O4 / MnWO4 (Mn3O4 / MnWO4@PDA) composite material; after drying, the composite material is subjected to carbonization and reduction treatment at 500°C for 5 h. After the reaction is completed, MnO / MnWO4@C is obtained.

[0043] 4): Mix MnO / MnWO4@C with selenium powder at a mass ratio of 1:5, grind them together, and put them into a ceramic boat. Place the ceramic boat in a tube furnace, and heat it to 650°C at a heating rate of 2°C / min under an argon atmosphere. After holding at this temperature for 2 hours, cool it to room temperature to obtain MnSe / MnWO4@C.

[0044] The obtained MnSe / MnWO4@C composite material was used to prepare MnSe / MnWO4@C modified separators for lithium-sulfur batteries: MnSe / MnWO4@C, acetylene black, and PVDF were mixed and ground in a mass ratio of 8:1:1, and then NMP was added to prepare a uniform slurry. This slurry was then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to obtain a MnSe / MnWO4@C modified separator.

[0045] Example 2 Preparation of MnSe / MnWO4@C composite materials: 1): Add 3.70 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 1.35 g MnSO4·H2O, 1.87 g (NH4)2S2O8 and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 100°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 / MnWO4 microspheres. 3): Take 100 mL of Tris solution, add 150 g of dopamine hydrochloride (DA) and 100 g of Mn3O4 / MnWO4 material to the Tris solution and stir in the dark to obtain Mn3O4 / MnWO4@PDA composite material; perform carbonization and reduction treatment on the composite material, and after the reaction is completed, obtain MnO / MnWO4@C.

[0046] 4): Mix and grind MnO / MnWO4@C with selenium powder at a mass ratio of 2:7, then place the mixture in a ceramic boat. Place the ceramic boat in a tube furnace and heat it to 650°C at a heating rate of 2°C / min under an argon atmosphere. After holding at this temperature for 3 hours, cool it to room temperature to obtain MnSe / MnWO4@C.

[0047] The obtained MnSe / MnWO4@C composite material was used to prepare MnSe / MnWO4@C modified separators for lithium-sulfur batteries: MnSe / MnWO4@C, acetylene black, and PVDF were mixed and ground in a mass ratio of 8:1:1, and then NMP was added to prepare a uniform slurry. This slurry was then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to obtain a MnSe / MnWO4@C modified separator.

[0048] Example 3 Preparation of MnSe / MnWO4@C composite materials: 1): Add 3.63 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 1.35 g MnSO4·H2O, 1.93 g (NH4)2S2O8 and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 105°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 / MnWO4 microspheres. 3): Take 100 mL of Tris solution, weigh 100 g of dopamine hydrochloride (DA) and 100 g of Mn3O4 / MnWO4 material, add them to the Tris solution and stir in the dark to obtain Mn3O4 / MnWO4@PDA composite material; subject the composite material to carbonization and reduction treatment, and after the reaction is completed, obtain MnO / MnWO4@C.

[0049] 4): Mix MnO / MnWO4@C with selenium powder at a mass ratio of 1:4, grind them together, and put them into a porcelain boat. Place the porcelain boat in a tube furnace, and heat it to 650°C at a heating rate of 2°C / min under an argon atmosphere. After holding at this temperature for 4 hours, cool it to room temperature to obtain MnSe / MnWO4@C.

[0050] The obtained MnSe / MnWO4@C composite material was used to prepare MnSe / MnWO4@C modified separators for lithium-sulfur batteries: MnSe / MnWO4@C, acetylene black, and PVDF were mixed and ground in a mass ratio of 8:1:1, and then NMP was added to prepare a uniform slurry. This slurry was then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to obtain a MnSe / MnWO4@C modified separator.

[0051] Example 4 Preparation of MnSe / MnWO4@C composite materials: 1): Add 3.68 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 1.45 g MnSO4·H2O, 1.9 g (NH4)2S2O8 and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 110°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 / MnWO4 microspheres. 3): Take 100 mL of Tris solution, weigh 70 g of dopamine hydrochloride (DA) and 100 g of Mn3O4 / MnWO4 material, add them to the Tris solution and stir in the dark to obtain Mn3O4 / MnWO4@PDA composite material; subject the composite material to carbonization and reduction treatment, and after the reaction is completed, obtain MnO / MnWO4@C.

[0052] 4): Mix and grind MnO / MnWO4@C with selenium powder at a mass ratio of 2:5, place the mixture in a ceramic boat, put the ceramic boat in a tube furnace, and heat it to 650°C at a heating rate of 2°C / min under an argon atmosphere. After holding at this temperature for 5 hours, cool it to room temperature to obtain MnSe / MnWO4@C.

[0053] The obtained MnSe / MnWO4@C composite material was used to prepare MnSe / MnWO4@C modified separators for lithium-sulfur batteries: MnSe / MnWO4@C, acetylene black, and PVDF were mixed and ground in a mass ratio of 8:1:1, and then NMP was added to prepare a uniform slurry. This slurry was then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to obtain a MnSe / MnWO4@C modified separator.

[0054] Example 5 Preparation of MnSe / MnWO4@C composite materials: 1): Add 3.78 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 1.55 g MnSO4·H2O, 1.89 g (NH4)2S2O8 and 0.8 g ammonium tungstate in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 120°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 / MnWO4 microspheres. 3): Take 100 mL of Tris solution, weigh 200 g of dopamine hydrochloride (DA) and 100 g of Mn3O4 / MnWO4 material, add them to the Tris solution and stir in the dark to obtain Mn3O4 / MnWO4@PDA composite material; subject the composite material to carbonization and reduction treatment, and after the reaction is completed, obtain MnO / MnWO4@C.

[0055] 4): Mix and grind MnO / MnWO4@C with selenium powder at a mass ratio of 1:3, then place the mixture in a ceramic boat. Place the ceramic boat in a tube furnace and heat it to 650°C at a heating rate of 2°C / min under an argon atmosphere. Hold the temperature for 6 hours and then cool it to room temperature to obtain MnSe / MnWO4@C.

[0056] The obtained MnSe / MnWO4@C composite material was used to prepare MnSe / MnWO4@C modified separators for lithium-sulfur batteries: MnSe / MnWO4@C, acetylene black, and PVDF were mixed and ground in a mass ratio of 8:1:1, and then NMP was added to prepare a uniform slurry. This slurry was then uniformly coated onto a commercial polypropylene separator for lithium-sulfur batteries to obtain a MnSe / MnWO4@C modified separator.

[0057] The MnSe / MnWO4@C membrane prepared according to this invention was used as a modified separator for lithium-sulfur batteries. The lithium-sulfur battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is MWCNTs / S, and the electrolyte is 1.0 M LiTFSI in DME: DOL = 1:1 Vol% with 1.0% LiNO3 solution. All assembly was performed in an argon-filled glove box. The rate performance and cycle performance of this lithium-sulfur battery were tested, showing good rate performance, cycle performance, and high specific capacity.

[0058] Comparison Example 1): Add 3.70 g of Tris powder to 1000 mL of deionized water, stir well, measure its pH value, add a small amount of hydrochloric acid to maintain its pH at 8.5, mix well, and obtain a Tris solution. 2): Dissolve 2.8 g MnSO4·H2O and 3.83 g (NH4)2S2O8 in 80 mL of deionized water and stir magnetically at room temperature for 40 min to obtain a precursor solution; transfer the well-stirred precursor solution to a reaction vessel and keep it at 105°C for 8 h; then wash and dry the precipitate to obtain Mn3O4 microspheres. 3): Take 100 mL of Tris solution, weigh 100 mg of dopamine hydrochloride (PDA) and 100 mg of Mn3O4 material, add them to the Tris solution and stir in the dark to obtain Mn3O4@PDA solution; after drying, the composite material is subjected to high-temperature carbonization and reduction treatment at 550°C for 5 h, and the reaction is completed to obtain MnO@C.

[0059] 4): Mix and grind 2 mmol MnO@C with 8 mmol selenium powder together and place the mixture in a ceramic boat. Place the ceramic boat in a tube furnace and heat it to 550°C at a heating rate of 2 °C / min under an argon atmosphere. Hold the temperature for 3 hours and then cool it to room temperature to obtain MnSe@C.

[0060] To verify the improvement effect of adding MnWO4 on the samples, this invention replicated the MnSe@C material through independent experiments for comparison, and compared the improvement of the cycle performance of lithium-sulfur batteries by the MnSe / MnWO4@C material. The embodiments and comparative examples are described below with reference to the accompanying drawings.

[0061] Figure 1These are X-ray diffraction patterns of MnSe / MnWO4@C prepared in Example 2 and the comparative counterexample MnSe@C; Figure 1 It can be seen that the sample MnSe / MnWO4@C contains both MnSe and MnWO4 phases, indicating that a composite / mixed-phase material has been successfully constructed; while the control sample MnSe@C mainly exhibits the MnSe phase.

[0062] Figure 2 These are Raman plots of MnSe / MnWO4@C prepared in Example 2 and the comparative counterexample MnSe@C; Figure 2 The presence of peaks D and G confirms the existence of a carbon layer, at 881.3 cm⁻¹. -1 The presence of the WO bond confirms that MnWO4 has been successfully introduced into the composite system.

[0063] Figure 3 These are SEM images of MnSe@C prepared in a comparative manner; Figure 3 It can be seen that the MnSe@C microspheres with a radius of about 5.2 to 5.7 μm have a nitrogen-doped carbon layer uniformly covering their surface.

[0064] Figure 4 This is a SEM image of MnO / MnWO4@C prepared in the preparation process (3) of Example 3; Figure 4 It can be seen that the MnO / MnWO4@C microspheres with a radius of about 4 to 5.1 μm are covered with a carbon layer on their surface.

[0065] Figure 5 Here is a SEM image of MnSe / MnWO4@C prepared in Example 3; Figure 5 It is known that the MnSe / MnWO4@C microspheres with a radius of approximately 4–5.1 μm are covered with carbon selenide particles on their surface.

[0066] Figure 6 This is a comparison chart of the rate performance of the MnSe / MnWO4@C composite modified membrane prepared in Example 3 and the MnSe@C composite modified membrane prepared in the comparative example and the commercial membrane at different current densities; Figure 6It can be seen that when the current is 150-200, 300-400, 750-1000, 1500-2000, and 3000-4000 mA / g, the corresponding specific capacities of the Li-S battery with the MnSe / MnWO4@C composite material modified separator are 1311.8, 1056.2, 943.1, 820.7, and 750.5 mAh / g, respectively. The corresponding specific capacities of the comparative Li-S battery with the MnSe@C composite material modified separator are 1243.8, 949.7, 870.7, 813.8, and 635.3 mAh / g. The corresponding specific capacities of the lithium-sulfur battery with the commercial blank separator are 934.0, 748.9, 650.2, 591.3, and 436.3 mAh / g. When the current density recovers to 300-400 mA / g, the specific capacities are... At this point, the specific capacity of the Li-S battery is 993.7, 730.6, and 627.2 mAh / g.

[0067] Figure 7 This is a comparison chart of the cycling performance of Li-S batteries with MnSe / MnWO4@C prepared in Example 3, MnSe@C composite material modified membrane prepared in the comparative example, and commercial membrane at 1 C current density; Figure 7 The cycling curves at 1 C (1500-2000 mA / g) show that the MnSe@C composite modified separators prepared in Experiment 3 and the comparative example retain a capacity of 700.3 and 293.4 mAh / g after 600 cycles, respectively, while the Li-S battery using a pure commercial separator retains a capacity of 210.3 mAh / g after 437 cycles. This demonstrates that the Li-S battery using the MnSe / MnWO4@C modified separator has excellent long-term cycling stability.

[0068] This invention describes preferred embodiments and their effects. However, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments.

[0069] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, characterized in that, Includes the following steps: Manganese sulfate, ammonium persulfate and ammonium tungstate were uniformly dispersed in an aqueous solvent to obtain a precursor solution, which was then used to synthesize Mn3O4 / MnWO4 microspheres via a hydrothermal method. Mn3O4 / MnWO4 microspheres and dopamine hydrochloride were reacted in Tris solution under light-protected stirring to obtain Mn3O4 / MnWO4@PDA composite material; The Mn3O4 / MnWO4@PDA composite material was carbonized to obtain MnO / MnWO4@C material; After mixing MnO / MnWO4@C material with a certain amount of selenium powder, it is subjected to selenization treatment in a high-temperature solid phase at 600~700°C to obtain carbon-coated manganese selenide / manganese tungstate composite material.

2. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 1, characterized in that, The mass ratio of manganese sulfate, ammonium persulfate, and ammonium tungstate is (1.35-1.55):(1.87-1.93):0.

8.

3. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 1, characterized in that, The hydrothermal synthesis process includes: sealing the precursor solution in a Teflon-lined stainless steel autoclave and holding it at 100~110℃ for 6~12h.

4. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 1, characterized in that, The Tris solution is prepared by placing tris(hydroxymethyl)aminomethane powder in an aqueous solvent and stirring to form a solution with a pH of 8-9; the concentration of the Tris solution is 0.03-0.0312 mol / L; the mass ratio of the Mn3O4 / MnWO4 microspheres to dopamine hydrochloride is 1:0.5-2.

5. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 1, characterized in that, The carbonization process involves heating the gas to 600-700°C at a rate of 2-3°C / min under argon atmosphere, holding it at that temperature for 1-2 hours, and then cooling it to room temperature.

6. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 1, characterized in that, High-temperature solid-phase selenization treatment includes: The MnO / MnWO4@C material is mixed with a certain amount of selenium powder and placed in a ceramic boat. The ceramic boat is placed in a tube furnace and heated to 600-700°C at a heating rate of 2-3°C / min under an argon atmosphere. After holding at this temperature for 1-2 hours, the temperature is lowered to room temperature.

7. The method for preparing the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties according to claim 6, characterized in that, The mass ratio of the MnO / MnWO4@C material to selenium powder is 1:3 to 1:

5.

8. A carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties prepared by the method according to any one of claims 1 to 7.

9. The application of the carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties as described in claim 8 in the preparation of lithium-sulfur batteries.

10. The application according to claim 9, characterized in that, A carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties was used to modify the polypropylene separator in a lithium-sulfur battery. The modification process included: A carbon-coated manganese selenide / manganese tungstate composite material with catalytic properties, acetylene black, and PVDF were mixed and ground in a mass ratio of (6~10):1:

1. NMP was then added to prepare a uniform slurry, which was then uniformly coated onto a polypropylene separator used in lithium-sulfur batteries to obtain a modified separator.